Odpowiedzi

2010-04-08T21:59:24+02:00
x-3(y-3x)=3x-4
{
2(2x-y)=4


x-3y+9x-3x=-4
{
4x-2y=4


7x-3y=-4
{
4x-2y=4 /:(-2)


7x-3y=-4
{
y=-2+2x

7x-3(-2+2x)=-4
7x+6-6x=-4
x=-10

y=-2+2*(-10)
y=-22

2010-04-08T22:00:25+02:00
{x-3y-9x=3x-4
{4x-2y=4

{8x-3y=3x-4
{4x-2y=4

{8x-3y-3x=-4
{4x-2y=4

{5x-3y=-4 I*-4
{4x-2y=4

{-20x+12y=4 I
{4x-2y=4 I

'''''''''''''''''''''''''''''''''''''''''''''''''''''''''''''''+'''''

-16x+10y=8


nie wiem czy dobrze....
2010-04-08T22:00:46+02:00
X-3(y-3)=3x-4
2(2x-y)=4

x-3y+9x=3x-4
4x-2y=4

7x-3y=-4/*2
4x-2y=4/*-3

14x-6y=-8
-12x+6y=-12
2x=-20/2
x=-10

7*-10-3y=-4
-70-3y=-4
-3y=66/-3
y=-22